2015
DOI: 10.1093/ehjci/jev302
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial oedema in acute myocarditis detected by echocardiographic 2D myocardial deformation analysis

Abstract: In patients with acute myocarditis, 2D speckle-tracking echocardiography was a useful tool in the diagnostic process of acute myocarditis. Global longitudinal strain adds important information that can support clinical and conventional echocardiographic evaluation, especially in patients with preserved LV ejection fraction in relation to the diagnosis and degree of myocardial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 26 publications
10
71
0
1
Order By: Relevance
“…One important effect of TNFα is its ability to modulate vascular leakiness as evidenced by studies demonstrating that elevated TNFα concentrations increase vascular permeability (Hansen et al, 1994). Increased vascular permeability can then lead to extracellular edema formation in tissue (Logstrup et al, 2015). In the heart, extracellular edema has been demonstrated to slow CV and increase arrhythmogenesis possibly due to reduced ephaptic coupling between myocytes (George and Poelzing, 2015; George et al, 2015; Veeraraghavan et al, 2015; George et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important effect of TNFα is its ability to modulate vascular leakiness as evidenced by studies demonstrating that elevated TNFα concentrations increase vascular permeability (Hansen et al, 1994). Increased vascular permeability can then lead to extracellular edema formation in tissue (Logstrup et al, 2015). In the heart, extracellular edema has been demonstrated to slow CV and increase arrhythmogenesis possibly due to reduced ephaptic coupling between myocytes (George and Poelzing, 2015; George et al, 2015; Veeraraghavan et al, 2015; George et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically, myocardial inflammation can cause cardiac dysfunction and reduced ejection fraction (Lurz et al, 2012; Banka et al, 2015). Myocardial inflammation can also alter electrical impulse propagation by modulating gap junctional coupling (GJC) (Zhu et al, 2000; Xu H. F. et al, 2012), ionic currents (Tang et al, 2007; De Jesus et al, 2015), and tissue hydration state (Logstrup et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…There is no any parameter predicting which patients are likely to recover and until the guideline published in 2013 by European Society of Cardiology that we are also using for both diagnosis and follow‐up of patients with acute viral myocarditis, the matter was a challenge somewhat . The diagnosis of acute myocarditis is based on symptoms, electrocardiography, elevated myocardial biomarkers, and ECHO . Pathological confirmation of myocardial inflammation continues to be required for a definitive diagnosis of myocarditis .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Khoo et al, impairment of the LV circumferential early diastolic strain rate additionally hinted at impaired LV diastolic function in the setting of MC [14]. Using the 17 segment model of the American Heart Association, another study showed reduced strain corresponding to intramyocardial edema in the basal inferior and inferolateral segments and in the midventricular anterior, anterolateral, and inferolateral segments in comparison to the other segments of the respective slice [15]. …”
Section: Speckle Trackingmentioning
confidence: 97%